Extreme Earth System Modelling on Maui - Williams, Jonny (The University of Auckland, 2019)
With the availability of NeSI’s new platforms, specifically Māui in this case, I will present results from our new earth system model. The model is complex to say the least, having a stratosphere-resolving atmosphere, global ocean, dynamic sea ice, atmospheric chemistry and ocean biology. This model is closely related to the one developed in the UK - the UKESM - but with the addition of a nested high resolution ocean model surrounding the New Zealand region. We plan to use this model to investigate the effect of ocean model resolution on marine heatwaves in our region. Getting this model running was a significant technical challenge and I will give an overview of how we got the model running. This is a highly collaborative exercise involving the UK climate modelling community, the Globus high speed data transfer network, a NeSI consultancy project and from the Deep South National Science Challenge.